Kedudukan Anak Perempuan dalam Hukum Waris Sunni dan Syiah: Kajian tentang Keadilan dan Penerapannya di Nusa Tenggara Barat - Suryadin, Suryadin; Arkiang, Bachder Syarif; Yumansyah, Diky; Zuhrah, Zuhrah (CV. Social Politic Genius (SIGn), 2025)
Islamic inheritance law constitutes a paradigmatic arena of debate concerning gender justice. This debate primarily concerns the position of daughters, which differs fundamentally between the Sunni and Shia schools of thought. This study has three objectives: first, to comparatively analyze the position of daughters in the legal constructions of Sunni and Shia inheritance law; second, to map the implementation of this law within the landscape of legal pluralism in West Nusa Tenggara; and third, to evaluate the materialization of gender justice in prevailing practices. This study employs a mixed-methods design with a sequential explanatory strategy. It combines doctrinal analysis of primary jurisprudential texts, an examination of court decisions, in-depth interviews with judges and customary leaders, and a survey of 150 heads of households in three representative locations in West Nusa Tenggara. The results reveal three layers of conflict. First, a philosophical conflict between the principles of ‘aṣabah (Sunni) and qarābah (Shia). Second, a variation in implementation at the judicial level, ranging from rigid-formalistic to adaptive-collaborative, which is heavily influenced by the hegemony of patriarchal customary law. Third, a quantitatively measured gender justice deficit caused by the interaction among the formalism of state law (the Compilation of Islamic Law), the dominance of patriarchal culture, and low gender literacy. It is concluded that gender injustice in inheritance practices in West Nusa Tenggara is structural. This problem cannot be resolved merely through the reform of legal texts but requires a holistic approach that includes critical education and the strengthening of substantive justice mechanisms.